Strength, speed and power characteristics of elite rugby league players - de Lacey, J.; Brughelli, M. E.; McGuigan, M. R.; Hansen, K. T. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this article was to compare strength, speed, and power characteristics between playing position (forwards and backs) in elite rugby league players. A total of 39 first team players (height, 183.8 ± 5.95 cm; body mass, 100.3 ± 10.7 kg; age, 24 ± 3 years) from a National Rugby League club participated in this study. Testing included 10-, 40-m sprint times, sprint mechanics on an instrumented nonmotorized treadmill, and concentric isokinetic hip and knee extension and flexion. Backs, observed to have significantly (p ? 0.05) lighter body mass (effect size [ES] = 0.98), were significantly faster (10-m ES = 1.26; 40-m ES = 1.61) and produced significantly greater relative horizontal force and power (ES = 0.87 and 1.04) compared with forwards. However, no significant differences were found between forwards and backs during relative isokinetic knee extension, knee flexion, relative isokinetic hip extension, flexion, prowler sprints, sprint velocity, contact time, or flight time. The findings demonstrate that backs have similar relative strength in comparison with forwards, but run faster overground and produce significantly greater relative horizontal force and power when sprinting on a nonmotorized instrumented treadmill. Developing force and power in the horizontal direction may be beneficial for improving sprint performance in professional rugby league players